Genetic (co)variance components for ratio of lamb weight to ewe metabolic weight as an indicator of ewe efficiency - Lôbo, Raimundo Nonato Braga; Júnior, Gerardo Alves Fernandes [UNESP]; Lôbo, Ana Maria Bezerra Oliveira; Facó, Olivardo (Elsevier, 2012)
Data from a multibreed commercial flock located at Mid-West of Brazil, supported by Programa de Melhoramento Genético de Caprinos e Ovinos de Corte (GENECOC), were used to estimate genetic parameters of traits related to ewe productivity by Average Information Restricted Maximum Likelihood method applied to an animal model. The analyzed traits were litter weight at birth (LWB) and at weaning (LWW), ewe weight at weaning (EW) and ewe production efficiency, estimated by WEE=LWW/EW 0.75. The heritabilities were 0.26±0.05, 0.32±0.06, 0.37±0.03 and 0.10±0.02 for LWB, LWW, EW and WEE, respectively. Significant effects for direct heterosis were observed for LWW and EW. Recombination losses were important for EW and WEE. Genetic correlations of LWB with LWW, EW and WEE were 0.68, 0.37 and 0.15, respectively; of LWW with EW and WEE were 0.30 and 0.34, respectively; and between EW and WEE was -0.25. Even though it is a low heritability trait, WEE can be indicated as a selection criteria for improving the ewe productivity without increasing the mature weight of animals due to its genetic correlations with LWW and other traits. © 2011 Elsevier B.V.
Keywords: Genetic correlation; Heritability; Multibreed flock; Non-additive effects; Sheep; Animalia; Ovis aries